Somatotype of elite Italian gymnasts - Massidda, M.; Toselli, S.; Brasili, P.; Calo, C. M. (Collegium Antropologicum, 2013)
The somatotyping method is especially helpful in sports in which the body could directly influence the biomechanics of movements and the performance`s results. The purpose of this study was to determine the somatotype of elite Italian gymnasts and to compare it in terms of competition levels. The sample comprised 64 elite gymnasts (42 females (F), somatotype 1.4-4.4-3.2; and 22 males (M), somatotype 1.6-6.3-2.1) belonging to the Italian National Artistic Gymnastic Team (2007) at different competition levels: Allieve, Junior, and Senior. Mean whole somatotypes, by competition levels, were not significantly different in both sexes (Female gymnasts: Allieve, 1.3-4.6-3.3; Junior, 1.3-4.2-3.6; Senior, 1.7-4.2-2.7; Male gymnasts: Junior, 1.5-6.3-2.5; Senior, 1.7-6.3-1.6). Male Junior gymnasts exhibited greater ectomorphy than Senior athletes (F1,20=7.75, p<0.01). Compared to other elite athletes male and female gymnasts tend to be less endomorphic and more mesomorphic. This study highlighted the peculiarities of the somatotype of Italian elite gymnasts and their strong homogeneity, evident also from the low values of somatotype attitudinal mean (SAM). The results emphasize the need for a specific somatotype to reach an elite level in sport and the need to integrate the somatotype analysis between the scientific instruments for selecting talent also in artistic gymnastics.